Antistatic high-thermal-conductivity flame-retardant PP material and preparation method thereof

By using a combination of polypropylene substrate, bio-based polymer, thermal filler, antistatic agent, smart flame retardant and functionalized nanoparticles in PP materials, the existing PP materials are solved after adding antistatic agent and thermal filler. The processing difficulty and appearance problems have achieved improvements in anti-static, high thermal conductivity and flame retardant performance, meeting the heat dissipation needs and sustainable development requirements of high-power electronic equipment.

CN119286131APending Publication Date: 2025-01-10SHANGHAI AIZHEN NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411534273.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

After adding antistatic agents and thermal conductivity fillers, existing PP materials are prone to problems of poor uniformity and poor fluidity, which increases processing difficulty and cost, and affects the toughness and appearance of the material, and cannot effectively meet the antistatic, high thermal conductivity and Flame retardant demand.

Method used

Using a combination of polypropylene substrate, bio-based polymer, thermal filler, antistatic agent, smart flame retardant, functionalized nanoparticles and toughener, through specific formula ratios and preparation processes, including vacuum drying, high-speed mixing, Melt extrusion and cooling to form an antistatic, highly thermally conductive and flame-retardant PP material.

Benefits of technology

Significantly improves the toughness and impact resistance of the material, improves the flowability and processing properties, ensures surface smoothness and appearance quality, improves physical and mechanical properties, expands applicability, and improves anti-static, thermal and flame retardant Performance, meet the heat dissipation needs and sustainable development requirements of high-power electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286131A_ABST
    Figure CN119286131A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of PP materials, and discloses an antistatic high-thermal-conductivity flame-retardant PP material and a preparation method thereof, the antistatic high-thermal-conductivity flame-retardant PP material comprises the following raw materials by weight: 60-70 parts of a polypropylene base material, 10-15 parts of a bio-based polymer, 10-15 parts of a thermal conductive filler, 2-5 parts of an antistatic agent, 5-10 parts of an intelligent flame retardant, 1-3 parts of functionalized nanoparticles, and 5 parts of a flexibilizer. By adding polyurethane, the toughness and impact resistance of the material are remarkably improved, it is ensured that the material is not prone to fracture when bearing external force, the product quality is guaranteed, aluminum nitride is selected as heat conduction filler, and the reasonable filler proportion is matched, so that the flowability and processing performance of the material are improved, the difficulty in the forming process is reduced, and the production cost is reduced; and finally, by adding the functionalized nanoparticles, the PP material keeps excellent performance, and the surface smoothness and the appearance quality of the material are ensured at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of PP materials, and specifically relates to an antistatic, high thermal conductivity, flame-retardant PP material and a preparation method thereof. Background Art

[0002] PP material, or polypropylene, is a thermoplastic synthetic resin with high density and crystallinity, which gives it high strength and hardness. At the same time, PP material is thermoplastic and can be softened and reshaped by heating, which gives it high flexibility and plasticity during processing, making PP material widely used in a variety of fields.

[0003] In industries such as electronic manufacturing, medical equipment, laboratories, and chemicals, the generation and accumulation of static electricity can lead to equipment damage, increased product defect rates, and even safety accidents. In some scenarios where heat dissipation is required, overheating can cause performance degradation or damage. In order to make PP materials transfer heat more effectively and have anti-static functions, an anti-static, high thermal conductivity, and flame-retardant PP material is usually required to meet the needs.

[0004] In order to meet the above requirements, current PP materials usually add antistatic agents and thermal conductive fillers during preparation to achieve antistatic and high thermal conductivity effects, which will increase the amount of fillers. However, after adding multiple fillers, composite materials with high filler content are prone to problems such as poor uniformity and poor fluidity during processing, which increases the difficulty and cost of processing. After adding fillers, it will affect its surface smoothness and appearance, making it not beautiful enough in some applications. More importantly, the toughness and strength of the material will decrease with the increase of fillers, so it needs to be improved and optimized. Summary of the invention

[0005] The object of the present invention is to provide an antistatic, highly thermally conductive, flame-retardant PP material and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0006] In order to achieve the above-mentioned purpose, the present invention provides the following technical scheme: an antistatic, highly thermally conductive, flame-retardant PP material and a preparation method thereof, which are composed of the following raw materials in parts by weight: 60-70 parts of a polypropylene substrate, 10-15 parts of a bio-based polymer, 10-15 parts of a thermally conductive filler, 2-5 parts of an antistatic agent, 5-10 parts of an intelligent flame retardant, 1-3 parts of functionalized nanoparticles and 5 parts of a toughening agent.

[0007] Preferably, the bio-based polymer is polylactic acid, the thermal conductive filler is aluminum nitride, the antistatic agent is polyetheramide, and the toughening agent is polyurethane.

[0008] Preferably, the functionalized nanoparticles are one of modified quantum dots and nano-silica, which are responsible for improving thermal and electrical conductivity and imparting optical properties to the material.

[0009] Preferably, the preparation process of the PP material is:

[0010] Step 1: accurately weigh the raw materials according to the formula ratio, and dry the polypropylene raw materials with strong hygroscopicity in a vacuum drying oven;

[0011] Step 2: Pour all solid raw materials into a high-speed mixer in sequence, set the stirring speed to 500 rpm, and mix for 10-20 minutes;

[0012] Step 3, after mixing evenly, melt extrusion is performed through a twin-screw extruder;

[0013] Step 4: The extruded material is quickly cooled by a cooling roller or a water tank to form sheets or particles to ensure that the material is fully formed;

[0014] Step five, cutting the extrudate into particles suitable for subsequent processing to complete the preparation.

[0015] Preferably, the intelligent flame retardant is a composite material of an organic phosphorus flame retardant and inorganic aluminum hydroxide, and the preparation steps are as follows:

[0016] A1, drying aluminum hydroxide in an oven at 100-120°C for 2-4 hours to remove moisture;

[0017] A2, adding dried aluminum hydroxide and triphenylphosphine into a mixer in a ratio of 2:1;

[0018] A3, mixer at 500 rpm for 10-20 minutes to ensure uniform dispersion;

[0019] A4, transfer the mixture into a high temperature resistant ceramic crucible and heat to 200-250°C for 30-60 minutes;

[0020] A5, place the processed composite material at room temperature to cool.

[0021] Preferably, in step three, the settings of the twin-screw extruder are: 150-180°C in the feeding zone, 180-220°C in the melting zone, 190-230°C in the homogenizing zone and 180-220°C in the die zone, wherein the extrusion pressure is 120 bar.

[0022] Preferably, the particle size of the PP material is controlled at 2-5 mm, and after preparation, the sample is tested for antistatic properties, thermal conductivity and flame retardancy to ensure that the design requirements are met.

[0023] Preferably, after the composite material of the organophosphorus flame retardant and the inorganic aluminum hydroxide is prepared, a grinder is used to crush the composite material into a desired particle size for subsequent mixing with a polymer matrix.

[0024] Preferably, the aluminum hydroxide in the composite material can effectively improve the thermal stability of the composite material and prevent the material from decomposing at high temperatures, thereby ensuring the stability and flame retardant effect of the material under high temperature conditions, while triphenyl phosphine suppresses flames by forming a carbonized layer and releasing flame-retardant gas.

[0025] The beneficial effects of the present invention are as follows:

[0026] 1. The present invention significantly improves the toughness and impact resistance of the material by adding polyurethane, ensures that it is not easy to break when subjected to external force, and ensures product quality. Then, by selecting aluminum nitride as a thermal conductive filler and matching a reasonable filler ratio, the fluidity and processing performance of the material are improved, the difficulty in the molding process is reduced, and the production cost is reduced. Finally, by adding functionalized nanoparticles, the PP material maintains excellent performance while ensuring the surface smoothness and appearance quality of the material. Through this comprehensive optimization design, not only the physical and mechanical properties of the material are improved, but also its applicability in different application fields is expanded, thereby improving product quality.

[0027] 2. The present invention adopts polyetheramide as an antistatic agent to make the antistatic effect of the material more stable under different environmental conditions, effectively maintain long-term antistatic performance, and reduce the risk of electrostatic discharge. At the same time, the introduction of aluminum nitride material can significantly improve thermal conductivity, meet the heat dissipation requirements of high-power electronic equipment, and avoid failures caused by heat accumulation. At the same time, the addition of bio-based polymers not only improves the stability and durability of the PP material in long-term use, but also ensures the environmental protection performance of the material and meets the needs of sustainable development.

[0028] 3. The present invention selects aluminum hydroxide and triphenylphosphine as the main components of the composite material, so that the two materials complement each other in flame retardant mechanism, enhances the synergistic effect of the two groups, improves the overall flame retardant performance, and can effectively improve the thermal stability of the composite material to prevent the decomposition of the material at high temperature. More importantly, this composite material is usually used so that when the temperature of the PP material exceeds a certain threshold, it can be effectively activated to provide continuous flame retardant protection and avoid the failure of traditional materials at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a flow chart for preparing the PP material of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] like Figure 1 As shown, an embodiment of the present invention provides an antistatic, highly thermally conductive, flame-retardant PP material and a preparation method thereof, which is composed of the following raw materials in parts by weight: 60-70 parts of a polypropylene substrate (PP resin), 10-15 parts of a bio-based polymer, 10-15 parts of a thermally conductive filler, 2-5 parts of an antistatic agent, 5-10 parts of an intelligent flame retardant, 1-3 parts of functionalized nanoparticles, and 5 parts of a toughening agent.

[0032] By adding polyurethane, the toughness and impact resistance of the material are significantly improved, ensuring that it is not easy to break when subjected to external force, thereby ensuring product quality. By selecting aluminum nitride as a thermal conductive filler and combining it with a reasonable filler ratio, the fluidity and processing performance of the material are improved, the difficulty of the molding process is reduced, and the production cost is reduced. Finally, by adding functionalized nanoparticles, the PP material maintains excellent performance while ensuring the surface smoothness and appearance quality of the material. This comprehensive optimization design not only improves the physical and mechanical properties of the material, but also expands its applicability in different application fields and improves product quality.

[0033] The bio-based polymer is polylactic acid (PLA), the thermal conductive filler is aluminum nitride (AlN), the antistatic agent is polyetheramide (PEA), and the toughening agent is polyurethane (TPU).

[0034] By adding polylactic acid (PLA), we can reduce the dependence on traditional petroleum-based materials and reduce the potential impact of materials on the environment, complying with increasingly stringent environmental regulations.

[0035] Among them, the functionalized nanoparticles are one of modified quantum dots and nano-silicon dioxide, which are responsible for improving thermal conductivity and electrical conductivity and giving optical properties to the material.

[0036] By improving the optical properties of the material, it has excellent functions in fields that need to ensure light transmission, such as lampshades.

[0037] Wherein, the preparation process of the PP material is:

[0038] Step 1: accurately weigh the raw materials according to the formula ratio, and dry the polypropylene raw materials with strong hygroscopicity in a vacuum drying oven;

[0039] Monitor the moisture content of raw materials to ensure it is less than 0.1% to prevent excessive moisture content, which may lead to bubble generation and poor material fluidity in subsequent processing;

[0040] Step 2: Pour all solid raw materials into a high-speed mixer in sequence, set the stirring speed to 500 rpm, and mix for 10-20 minutes;

[0041] During the mixing process, agglomerated fillers or additives may cause excessive concentration in certain areas of the material, thereby reducing the performance of these areas and affecting the overall strength and stability of the product. Therefore, it is necessary to regularly check the uniformity of the mixture to avoid agglomeration;

[0042] Step 3, after mixing evenly, melt extrusion is performed through a twin-screw extruder;

[0043] During extrusion, three heating zones are set to heat gradually to ensure that the material melts evenly and thoroughly;

[0044] Step 4: The extruded material is quickly cooled by a cooling roller or a water tank to form sheets or particles to ensure that the material is fully formed;

[0045] Step five, cutting the extrudate into particles suitable for subsequent processing to complete the preparation.

[0046] By using polyetheramide as an antistatic agent, the antistatic effect of the material is made more stable under different environmental conditions, which can effectively maintain long-term antistatic performance and reduce the risk of electrostatic discharge. At the same time, the introduction of aluminum nitride material can significantly improve the thermal conductivity, meet the heat dissipation needs of high-power electronic equipment, and avoid failures caused by heat accumulation. At the same time, the addition of bio-based polymers not only improves the stability and durability of the PP material in long-term use, but also ensures the environmental performance of the material and meets the needs of sustainable development.

[0047] The intelligent flame retardant is a composite material of an organic phosphorus flame retardant and inorganic aluminum hydroxide, and its preparation steps are as follows:

[0048] A1, drying aluminum hydroxide in an oven at 100-120°C for 2-4 hours to remove moisture;

[0049] Drying treatment ensures the smooth progress of subsequent reactions and compounding;

[0050] A2, adding dried aluminum hydroxide and triphenylphosphine into a mixer in a ratio of 2:1;

[0051] Aluminum hydroxide releases water when it decomposes at high temperatures, which can dilute the combustible gas and form a protective char layer, while triphenyl phosphine suppresses the flame by forming a char layer and releasing flame-retardant gas;

[0052] A3, mixer at 500 rpm for 10-20 minutes to ensure uniform dispersion;

[0053] A4, transfer the mixture into a high temperature resistant ceramic crucible and heat to 200-250°C for 30-60 minutes;

[0054] Heat treatment is performed to promote a chemical reaction between the organic phosphorus and the inorganic aluminum hydroxide to form a stable composite material;

[0055] A5, place the processed composite material at room temperature to cool.

[0056] Avoid material rupture caused by rapid cooling, provide more efficient flame retardant performance, and automatically activate at high temperatures to ensure the safety of the material under extreme conditions;

[0057] By selecting aluminum hydroxide and triphenylphosphine as the main components of the composite material, the two materials complement each other in flame retardant mechanism, enhance the synergistic effect of the two groups, improve the overall flame retardant performance, and effectively improve the thermal stability of the composite material to prevent the decomposition of the material at high temperature. More importantly, this composite material is usually used so that when the temperature of the PP material exceeds a certain threshold, it can be effectively activated to provide continuous flame retardant protection and avoid the failure of traditional materials at high temperatures.

[0058] Wherein, in the step three, the settings of the twin-screw extruder are: feeding zone 150-180°C, melting zone 180-220°C, homogenization zone 190-230°C and mold zone 180-220°C, wherein the extrusion pressure is 120 bar.

[0059] By setting four heating zones, the temperature of each heating zone can be gradually increased so as to better control the melting and mixing process of the materials.

[0060] The particle size of the PP material is controlled at 2-5 mm, and after preparation, the sample is tested for antistatic properties, thermal conductivity and flame retardancy to ensure that the design requirements are met.

[0061] Among them, the antistatic test uses a surface resistivity meter to measure the surface resistance of the material to ensure that it meets 10^6-10^9Ω. The thermal conductivity test ensures that the performance reaches above 1W / m·K. The flame retardant performance test uses a vertical burning test to evaluate the flame retardant level of the material to ensure that it meets industry standards.

[0062] After the composite material of the organic phosphorus flame retardant and the inorganic aluminum hydroxide is prepared, a grinder is used to crush the composite material into a desired particle size (usually 100-200 microns) for subsequent mixing with a polymer matrix.

[0063] Among them, the aluminum hydroxide in the composite material can effectively improve the thermal stability of the composite material and prevent the decomposition of the material at high temperature, thereby ensuring the stability and flame retardant effect of the material under high temperature conditions, while triphenyl phosphine suppresses flames by forming a carbonized layer and releasing flame-retardant gas.

[0064] The addition of polyurethane significantly improves toughness and impact resistance, ensuring that it is not easy to break when subjected to external forces, thereby improving product quality. The use of aluminum nitride as a thermal conductive filler and the reasonable configuration of the filler ratio improve the fluidity and processing performance of the material, reducing the difficulty of molding and production costs. At the same time, the introduction of functionalized nanoparticles ensures the surface smoothness and elegant appearance of the material, further broadening its application areas. Its outstanding performance in antistatic, thermal conductivity, flame retardancy, etc. makes it suitable for multiple industries such as electronics, automobiles, and construction, meeting the modern market's demand for high-performance and sustainable materials.

[0065] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0066] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An antistatic, high thermal conductivity, flame retardant PP material, characterized by: The invention is composed of the following raw materials in parts by weight: 60-70 parts of polypropylene substrate, 10-15 parts of bio-based polymer, 10-15 parts of thermal conductive filler, 2-5 parts of antistatic agent, 5-10 parts of intelligent flame retardant, 1-3 parts of functionalized nanoparticles and 5 parts of toughening agent.

2. The antistatic, high thermal conductivity, flame-retardant PP material according to claim 1, characterized in that: The bio-based polymer is polylactic acid, the thermal conductive filler is aluminum nitride, the antistatic agent is polyether amide, and the toughening agent is polyurethane.

3. The antistatic, high thermal conductivity, flame-retardant PP material according to claim 1, characterized in that: The functionalized nanoparticles are one of modified quantum dots and nano-silicon dioxide, responsible for improving thermal and electrical conductivity and giving the material optical properties.

4. The method for preparing an antistatic, high thermal conductivity, flame-retardant PP material according to claim 1, characterized in that: The preparation process of the PP material is as follows: Step 1: accurately weigh the raw materials according to the formula ratio, and dry the polypropylene raw materials with strong hygroscopicity in a vacuum drying oven; Step 2: Pour all solid raw materials into a high-speed mixer in sequence, set the stirring speed to 500 rpm, and mix for 10-20 minutes; Step 3, after mixing evenly, melt extrusion is performed through a twin-screw extruder; Step 4: The extruded material is quickly cooled by a cooling roller or a water tank to form sheets or particles to ensure that the material is fully formed; Step five, cutting the extrudate into particles suitable for subsequent processing to complete the preparation.

5. The method for preparing an antistatic, high thermal conductivity, flame-retardant PP material according to claim 4, characterized in that: The intelligent flame retardant is a composite material of an organic phosphorus flame retardant and inorganic aluminum hydroxide, and its preparation steps are as follows: A1, drying aluminum hydroxide in an oven at 100-120°C for 2-4 hours to remove moisture; A2, adding dried aluminum hydroxide and triphenylphosphine into a mixer in a ratio of 2:1; A3, mixer at 500 rpm for 10-20 minutes to ensure uniform dispersion; A4, transfer the mixture into a high temperature resistant ceramic crucible and heat to 200-250°C for 30-60 minutes; A5, place the processed composite material at room temperature to cool.

6. The method for preparing an antistatic, high thermal conductivity, flame-retardant PP material according to claim 4, characterized in that: In step 3, the twin-screw extruder is set as follows: 150-180° C. in the feeding zone, 180-220° C. in the melting zone, 190-230° C. in the homogenizing zone and 180-220° C. in the die zone, wherein the extrusion pressure is 120 bar.

7. The method for preparing an antistatic, high thermal conductivity, flame-retardant PP material according to claim 4, characterized in that: The particle size of the PP material is controlled at 2-5 mm, and after preparation, the samples are tested for antistatic properties, thermal conductivity and flame retardancy to ensure that the design requirements are met.

8. The method for preparing an antistatic, high thermal conductivity, flame-retardant PP material according to claim 5, characterized in that: After the composite material of the organic phosphorus flame retardant and the inorganic aluminum hydroxide is prepared, a grinder is used to crush the composite material into a desired particle size for subsequent mixing with a polymer matrix.

9. The method for preparing an antistatic, high thermal conductivity, flame-retardant PP material according to claim 5, characterized in that: The aluminum hydroxide in the composite material can effectively improve the thermal stability of the composite material and prevent the material from decomposing at high temperatures, thereby ensuring the stability and flame retardant effect of the material under high temperature conditions, while the triphenyl phosphine suppresses flames by forming a carbonized layer and releasing flame-retardant gas.